A novel design for porphyrin based D–s–A systems as molecular rectifiers. Issue 2 (8th December 2015) - Garg, Kavita; Majumder, Chiranjib; Gupta, Shiv K.; Aswal, Dinesh Kumar; Nayak, Sandip Kumar; Chattopadhyay, Subrata
Abstract : Electro-grafted porphyrin-based D–s–A monolayers on Si behave as rectifiers. Abstract : Two Si-based hybrid self-assembled monolayers of porphyrin based on a D–s–A system were synthesized by electro-grafting. The monolayers showed a stable and reversible rectification at room temperature. The monolayer fabricated using a porphyrin with an eleven-carbon alkyl chain linker was comparatively more compact and exhibited a 10 5 times higher rectification ratio (RR) relative to another similar system that had a six-carbon alkyl chain linker, possibly because of the compact packing.